Pendampingan Pembuatan dan pengembangan Branding Pckaging untuk Bank Sampah Rukmi kelurahan Gunung Anayar Tambak - Tito Widiandaru; Ignatia Martha Hendrati; Anisa Fitria Utami (Literasi: Jurnal Pengabdian Masyarakat dan Inovasi, 2022)
The perpetrators of MSMEs in the Garbage Bank of Gunung Anayar Tambak Village have not developed towards Branding Pckaging every year. In its development, MSMEs need Branding Pcakaging for product packaging for scented candles from waste banks. However, MSME actors in Gunung Anyar Tambak are still lacking in knowledge and mechanisms for making branding packaging. This community service activity aims to solve these problems, which aims to introduce, increase knowledge and assist MSME actors in making branding packaging. The implementation method used there are 3 stages, namely socialization, training and mentoring. The implementation of the activities includes the delivery of theory, making branding packaging for the business being developed. The results of this activity are the MSME actors in Gunung Anayar Tambak Village, Surabaya City showing an increase in knowledge about business legality.